2009
DOI: 10.1007/s11250-009-9332-9
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence estimation and management factors associated with high herd seropositivity for Anaplasma marginale in commercial dairy farms of Puerto Rico

Abstract: A cross-sectional study was conducted to determine individual cow seroprevalence of Anaplasma marginale in adult lactating dairy cattle of Puerto Rico (PR) and to assess the associations of farm management factors on herd seroprevalence. Antibody activity against A. marginale was determined using the MSP-5 competitive enzyme-linked immunosorbent assay. Serum samples were obtained from 2,414 adult lactating dairy cattle from 76 randomly selected commercial dairy farms. Herd seroprevalence ranged from 3 to 100% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 27 publications
2
24
1
Order By: Relevance
“…This was slightly lower than the MSP-5 cELISA seroprevalence of 27% estimated within this sample 32 and toward the lower end of the range of prevalence reported for the Caribbean region. 5 There was a very low prevalence of cattle positive by direct examination of Wright-Giemsa-stained blood smears (5/2331) suggesting few acute infections and possible endemic stability within some herds on the island.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…This was slightly lower than the MSP-5 cELISA seroprevalence of 27% estimated within this sample 32 and toward the lower end of the range of prevalence reported for the Caribbean region. 5 There was a very low prevalence of cattle positive by direct examination of Wright-Giemsa-stained blood smears (5/2331) suggesting few acute infections and possible endemic stability within some herds on the island.…”
Section: Discussioncontrasting
confidence: 71%
“…32 In brief, commercial dairy farms in Puerto Rico constituted the list frame and were randomly selected after stratification by the 4 major ecological zones of the island and the 3 herd sizes. Lactating cattle within herds were randomly selected based on either a simple random sample or systematically as cattle exited the milking parlor.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catttle of more than 4 year of age were significantly (P<0.05) at higher risk as compared to <2-4, 1-2 and <1 year age groups (Atif et al, 2013). (Urdaz-Rodriguez et al, 2009;Aubry and Geale, 2011) mentioned seroprevalence increased with age found higher prevalence of anaplasmosis in calves and lowest in young cattle in Uganda and the difference was explained by dominant immune responses to Anaplasma spp. infection.…”
Section: Agementioning
confidence: 99%
“…Following transmission, cattle develop rickettsiaemia, accompanied by fever, severe anemia, weight loss, decreased milk production, abortion and sometimes death during acute infections (Kocan et al, 2003;Urdaz-Rodríguez et al, 2009). After the first infection with A. marginale, cattle remain persistently infected carriers and serve as long-term reservoirs for the maintenance of the infection in ticks (Goff et al, 1988;Kocan et al, 1992a,b;Eriks et al, 1993).…”
Section: Introductionmentioning
confidence: 99%